The associations of unsweetened, sugar-sweetened, and artificially sweetened tea consumption with all-cause and cause-specific mortality in 195,361 UK Biobank participants: a large prospective cohort study - Huang, Hao; Zhang, Lei; Zhang, Ding; Yang, Miaomiao; Lin, Ying; Wang, Zhiyong; Wei, Pei; Lin, Jiaqi; Huang, Jingyao; Wei, Pengfei; Chen, Yinggang; He, Baochang; et al. (Frontiers in Nutrition, 2025)
BackgroundTea consumption has been associations with a lower risk of mortality and numerous health benefits. However, it is still unclear whether consuming tea with or without sugar or sweeteners has different effects on mortality. It is necessary to investigate the associations of unsweetened, sugar-sweetened, and artificially sweetened tea consumption with all-cause mortality and cause-specific mortality.MethodsIn this population-based cohort study of 195,361 UK Biobank participants who completed at least one 24-h dietary recall, we examined tea consumption by type (unsweetened, sugar-sweetened, artificially sweetened). Cox proportional hazards models and restricted cubic splines were used to assess nonlinear associations between tea intake and the risks of all-cause, cancer, and cardiovascular disease (CVD) mortality. We also conducted subgroup analyses stratified by genetic score for caffeine metabolism.ResultsAfter a median follow-up of 13.6 years, 11,718 all-cause deaths were recorded, including 2,202 deaths from CVD and 6,415 from cancer. A U-shaped association was observed between tea consumption and mortality risk. Compared with non-consumers, individuals consuming 3.5–4.5 drinks per day of unsweetened tea had the lowest risks of all-cause (HR, 0.80; 95% CI: 0.75–0.86), cancer (HR, 0.86; 95% CI: 0.77–0.97), and CVD (HR, 0.73; 95% CI: 0.60–0.89). Sugar-sweetened tea showed no consistent or statistically significant associations with all-cause, cancer, or CVD mortality across different levels of consumption. Similarly, no significant associations were found for artificially sweetened tea. The observed associations between tea consumption and mortality were not modified by genetic predisposition to caffeine metabolism.ConclusionUnsweetened tea consumption was significantly associated with a lower risk of all-cause, cancer, and CVD mortality. No consistent or statistically significant associations were observed for sugar-sweetened or artificially sweetened tea. The potential attenuation of tea’s protective effects by added sugar or artificial sweeteners warrants further investigation. Given current evidence, it may be advisable to consume tea without added sweeteners to optimize health benefits and longevity.